Architecture and Landscape in the Andean World; Universal Values: The Sondondo Valley (Ayacucho, Peru) - Elia Sáez; José Canziani (Buildings, 2025)
This study examines the cultural landscape of the Sondondo Valley in the Andes Mountains range of Peru, highlighting its significant ecological, landscape, and architectural worth. The valley’s representativeness of Andean culture and worldview, the lifestyle of its inhabitants, and the sustainability inherent in the connection between the population and the territory render it a space of universal values. The distinctive attributes of scale, conservation, continuity, and the remarkable landscape resulting from specialized territorial management dating back to pre-Hispanic origins provide the foundation for its inclusion, supported by our study, in the UNESCO indicative list of World Heritage. Through an extensive research initiative, both in time and intensity, and residence in the site as the source of essential research material, we accomplished a cross-scalar analysis that connects territory to architecture, providing tools for landscape intervention through planning and design, aimed at its enhancement and preservation. This document presents the findings of the investigation and the significance of this remarkable cultural landscape.